Blocks as Geographic Discontinuities: The Effect of Polling-Place Assignment on Voting. (3rd August 2022) - Tomkins, Sabina; Yao, Keniel; Gaebler, Johann; Konitzer, Tobias; Rothschild, David; Meredith, Marc; Goel, Sharad
Abstract: A potential voter must incur a number of costs in order to successfully cast an in-person ballot, including the costs associated with identifying and traveling to a polling place. In order to investigate how these costs affect voter turnout, we introduce two quasi-experimental designs that can be used to study how the political participation of registered voters is affected by differences in the relative distance that registrants must travel to their assigned Election Day polling place and whether their polling place remains at the same location as in a previous election. Our designs make comparisons of registrants who live on the same residential block, but are assigned to vote at different polling places. We find that living farther from a polling place and being assigned to a new polling place reduce in-person Election Day voting, but that registrants largely offset for this by casting more early in-person and mail ballots.